Evaluation of geocomposite base stabilization on lateritic gravel and granular material bases using accelerated pavement testing - Pedroso, G. O. M. [UNESP]; Silva, J. Lins da; Biondi, G.; Cazzuffi, D.; Moraci, N.; Soccodato, C. (Crc Press-taylor & Francis Group, 2024)
This study presents a laboratory study on seven different test configurations subjected to cycling moving wheels load by using an accelerated pavement test. Tests were conducted on lateritic clay mixed with gravel and unbounded granular material at two different thickness, in a geosynthetic stabilized and unstabilized sections. All test sections were constructed on a low CBR clay subgrade. Each pavement section performance was evaluated by measuring the surface rutting and the subgrade vertical pressure at different cycles. Findings indicated that the lateritic gravel base pavement sections had lower surface rutting than the granular base, mainly because the lateritic increases the material stability, delaying the occurrence of damage on the gravel. Furthermore, sections modified with geocomposite were found to have improved performance than the control sections.